INTEGRATING AKHLAKUL KARIMAH VALUES FROM HILYAH THĀLIB AL-‘ILMI IN PESANTREN-BASED CHARACTER EDUCATION - Abdurrahman, Abdurrahman; Asse, Ambo; Das, St. Wardah Hanafie; Jurumiah, Abdul Hakim (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Purpose: This study analyzes the implementation of akhlakul karimah values in the book Hilyah Thālib al-‘Ilmi by Syaikh Bakr bin ‘Abdullah Abu Zayd in shaping the character of students at Pesantren Abu Bakar Ash-Shiddiq Wahdah Islamiyah Bulukumba. Method: The research employed a qualitative approach with a case study design. Data were collected through interviews, participatory observation, and documentation, and then analyzed thematically. Result: The findings indicate that the book effectively enhances students’ discipline, responsibility, respect for teachers, and social etiquette. The internalization of values occurs through modeling, advice, and practical habituation, although social media and global culture present significant challenges. Conclusion: The study confirms the relevance of classical texts as instruments for character education and recommends innovative teaching methods to align with the needs of today’s youth. Implication: The contribution of this research lies in strengthening the position of Hilyah Thālib al-‘Ilmi as a strategic reference in Islamic boarding school education and offering a character curriculum development model that is adaptive to the challenges of the globalization era.